Activation of Fibrinolysis and of Plasma-Kinin System during Venostasis* - Buluk, K; Malofiejew, M; Czokalo, Maria (Thrombosis and Haemostasis, 1965)
In the plasma of stasis blood, fibrinolytic activity increases as a result of the enrichment of this blood by fibrinolysis activators of tissue origin. With the increase in fibrinolytic activity an increase in kallikrein and a temporary release of plasma kinin occurs. Plasma kallikrein, activated in the stasis blood through fibrinolysis activation on application of a manometric cuff retains its activity and may play some role in the lowering of blood pressure when the cuff is removed.